2021
DOI: 10.1016/j.msea.2020.139989
|View full text |Cite
|
Sign up to set email alerts
|

Strength, fatigue strength and toughness of dissimilar Ti17–Ti64 linear friction welded joints: Effect of soft surface contamination and depletion of α precipitates

Abstract: The effect of microstructure of three dissimilar Ti17-Ti64 linear friction welded joints on the strength, fatigue strength and fracture toughness was studied. A special attention was paid to role of soft contaminants and α precipitate depletion. Three joints were produced: one in the as machined state after electrical discharge machining, one ground prior to welding, and one welded in the as machined state and post-weld heat treated. The microstructure of the weld centre zone (WCZ) exhibited an acicular entang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Previous studies on LFW of titanium alloy joints (similar and dissimilar) have also applied different microscopic techniques (e.g., optical, SEM) to link the microstructural transformation to the hardness evolution [ 10 , 11 , 15 , 22 , 26 , 27 , 40 , 48 , 49 , 50 ]. A particularly favored method for linear friction welds is the use of electron backscatter diffraction (EBSD) to map the orientation of the α-phase grains [ 13 , 18 , 23 , 26 , 27 , 28 , 51 , 52 ]; this method allows visual differentiation of the WC (with its recrystallized fine grain structure of α′ martensite) and the TMAZs (with their plastically deformed and elongated α-grain structure) from the bimodal BM microstructure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on LFW of titanium alloy joints (similar and dissimilar) have also applied different microscopic techniques (e.g., optical, SEM) to link the microstructural transformation to the hardness evolution [ 10 , 11 , 15 , 22 , 26 , 27 , 40 , 48 , 49 , 50 ]. A particularly favored method for linear friction welds is the use of electron backscatter diffraction (EBSD) to map the orientation of the α-phase grains [ 13 , 18 , 23 , 26 , 27 , 28 , 51 , 52 ]; this method allows visual differentiation of the WC (with its recrystallized fine grain structure of α′ martensite) and the TMAZs (with their plastically deformed and elongated α-grain structure) from the bimodal BM microstructure.…”
Section: Resultsmentioning
confidence: 99%
“…This explains the observations of García and Morgeneyer [ 33 ] in their study of the fatigue performance of Ti6242 linear friction welds that exhibited low fatigue strength values, as well as premature/early failures due to remnant porosity at the joint interface. Recently, Garcia et al [ 11 ] also reported on the detrimental impact of defects—such as oxides, pores and contaminants that remain in the joint and originate from inadequate preparation of the faying surfaces prior to LFW—on the fatigue behavior of dissimilar Ti17–Ti64 linear friction welds that failed prematurely at a very low number of cycles or within the first fatigue cycle. Moreover, their work indicated that in the presence of defects, the application of PWHT to relieve residual stresses or modify the microstructure was ineffective in overcoming the compromised fatigue resistance from poor weld integrity, which aligns precisely with the expected outcome from the structural hierarchy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this assumes that Young's modulus of the studied material is known and constant, which is not the case for cross‐weld specimens. [ 8–10 ] An analytical expression of the stress field induced in fatigue specimens as function of the displacement field imposed by the misaligned load frame, in particular the bending deflection, is required.…”
Section: Introductionmentioning
confidence: 99%